Comparative analysis of educational development in the world - Solijonov Yorqinjon Gayrat oglu (Genius Journals, 2025)
The article provides a comparative analysis of the development trends of regional education systems in the modern world. The examples of the USA, South Korea, India, Finland and Uzbekistan reveal the distinctive aspects of the systems in five main groups (West, East Asia, developing countries, Scandinavia, Middle East and Central Asia). The analysis identifies economic resources, cultural principles, policies and innovations, and social equality as factors influencing the development of education. The conclusion highlights the reasons for the differences in global education and the lessons learned from interregional experiences. The article serves to understand changes in world education and create an empirical basis for national reforms
Keywords: Education system; Comparative analysis; Regional models